The Use of Stationary Underwater Video for Sampling Sharks - Harvey, Euan; Santana Garcon, J.; Goetze, Jordan; Saunders, Ben; Cappo, M. (CRC Press, 2018)
This pioneering book, written by experts in shark biology, examines technologies such as autonomous vehicle tracking, underwater video approaches, molecular genetics techniques, and accelerometry, among many others.